Analisis Hubungan antara Pendapatan, Dana Pihak Ketiga, dan Return On Asset dengan Tingkat Bagi Hasil Deposito Mudharabah - Ali, Haedar (Institut Agama Islam Negeri Surakarta, 2018)
Income, DPK, ROA and profit sharing rate of mudharabah deposits is a component of bank balance sheet that is hypothesized to have a certain relationship. By knowing the relationship, can be used as information for managers in decision making. This study aims to analyze whether or not there is a relationship between Income, DPK, and ROA with profit sharing rate of mudharabah deposits. The data was taken by BNI Sharia quarterly reports from 2010 to 2015. The data was analyzed by Pearson's correlation. This study found that income had a relationship with profit sharing rate of mudharabah deposits, while DPK and ROA has no relationship with profit sharing rate of mudharabah deposits. The research gives contribution for (a) academician; as an evidence of theory, (b) Banks Manager;information to make a decision.